SISTEM MANAJEMEN BASIS DATA DAN KUALITAS PENGAMBILAN KEPUTUSAN - Fitri, Amalia Diana (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
The main problem in data management is how to store, manage and access data efficiently, consistently, structured and securely in various usage environments. This becomes increasingly important as the volume and complexity of data that must be processed in a short time increases. The purpose of this paper is to examine the basic concepts of databases and the role of database management systems in supporting data storage, processing and utilization needs in various fields, both organizations and industry. The research was carried out through a literature study approach to various sources that discuss the structure, function and characteristics of modern data management systems. The study results show that the database management system provides a systematic mechanism for data management, enabling control of integrity, security, data recovery, as well as ease of access for users with various needs. In conclusion, implementing a database management system correctly can increase operational efficiency, minimize errors, and support information-based decision making that is accurate, relevant, and reliable